2015
DOI: 10.1017/s1366728915000401
|View full text |Cite
|
Sign up to set email alerts
|

Dislocations in French–English bilingual children: An elicitation study

Abstract: This paper presents the results of two sentence production studies addressing the role of language exposure, prior linguistic modelling and discourse-pragmatic appropriateness on the phenomenon of cross-linguistic influence (CLI) in bilingual 5-year-olds. We investigated whether French–English bilingual children would be as likely as monolingual children to use a left-dislocation structure in the description of a target scene. We also examined whether input quantity played a role in the degree of accessibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 66 publications
(104 reference statements)
7
45
2
Order By: Relevance
“…Another possibility is that 33 inhibitory mechanisms only prevent access to the shared syntactic representations when the prime and target are not an equally good option in the two languages. Accordingly, Vasilyeva et al (2010) were not able to prime fue-passives from English to Spanish and Hervé et al (2015) report that the effect of priming is significantly weaker when the primed structure is not pragmatically felicitous in the target language. In the latter study, English-French bilinguals produced pragmatically odd left-dislocations in English as a result of priming, but the effect was significantly weaker than in French, where priming did not lead to the production of inappropriate forms.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Another possibility is that 33 inhibitory mechanisms only prevent access to the shared syntactic representations when the prime and target are not an equally good option in the two languages. Accordingly, Vasilyeva et al (2010) were not able to prime fue-passives from English to Spanish and Hervé et al (2015) report that the effect of priming is significantly weaker when the primed structure is not pragmatically felicitous in the target language. In the latter study, English-French bilinguals produced pragmatically odd left-dislocations in English as a result of priming, but the effect was significantly weaker than in French, where priming did not lead to the production of inappropriate forms.…”
Section: Discussionmentioning
confidence: 86%
“…Hervé et al (2015) conclude that bilingual children are sensitive to the relative frequency of the structure in their languages; however, crosslinguistic influence takes place and increases as a function of language exposure; in addition, they suggest that priming can override discourse-pragmatic constraints in bilingual children, but not in monolingual children.…”
Section: Priming In Bilingual Childrenmentioning
confidence: 82%
See 2 more Smart Citations
“…Crucially, Hsin et al (2013) showed that syntactic constructions are shared across languages even in the absence of structural overlap, as Spanish-English children were successfully primed to use the English Adj+N word order in Spanish, a language in which the canonical word order for adjectives is postnominal. Hervé et al (2015) indicated that bilingual children are sensitive to the frequency of syntactic structures in their input as language exposure affected the likelihood of producing a left-dislocation in both optimal (French) and sub-optimal (English) discourse contexts. Overall, the processing account considers the possibility of bi-directional CLI in any language combination as a result of the interaction Determiner development in French-English children 5 between the two competing linguistic systems.…”
mentioning
confidence: 99%